Extraction of photovoltaic module model's parameters using an improved hybrid differential evolution/electromagnetism-like algorithm - Muhsen D.H.; Ghazali A.B.; Khatib T.; Abed I.A. (Elsevier Ltd, 2023)
Algorithms; Evolutionary algorithms; Mean square error; Optimization; Parameter estimation; Photovoltaic cells; Coefficient of determination; DEAM; Five parameters; Hybrid differential evolution; Improved differential evolutions; IV characteristics; Photovoltaic modules; Root mean square errors; Iterative methods; algorithm; artificial intelligence; electromagnetic method; error analysis; experimental study; photovoltaic system